Perceptions of spirituality in Australian undergraduate nursing students: A pre- and post-test study - Violeta Lopez; Maria Cynthia Leigh; Imke Fischer; David Larkin; Sue W ebster (Tehran University of Medical Sciences, 2015)
Background & Aim: Spiritual care is an integral part of a holistic nursing care. Providing spiritual care has a positive impact on patients' health outcomes. Although nurses understand the importance of incorporating  patient's  spiritual  beliefs  into the care practice,  understanding  their  spirituality before addressing the spirituality of patients is also important. Therefore, the aim of this study was to examine where there was a change in the undergraduate nursing students' perceptions of spiritu- ality care following a spirituality teaching unit in the Bachelor of Nursing course delivered in the Australian context. Methods & Materials: A total of 113 nursing students completed the pre- and post-survey. The validated 32-items World Health Organization Quality of Life-Spirituality, Religiosity, and Person- al Belief (SPRB) questionnaire were used in this study. Data were analyzed using SPSS version 20 using descriptive statistics and paired t-test. Results: There were significant differences in students' perceptions of SRPB in all eight dimen- sions and total spirituality score. Significant differences were also found in students' perceptions of the SRPB scores by religious beliefs (P < 0.0005) and personal beliefs (P < 0.0005), indicating students with strong religious and personal beliefs had strong SRPB scores. Conclusion: The integration of spirituality education in the undergraduate nursing program provid- ed insights on spiritual teaching in nursing education.